Something wicked this way comes - Bradbury, Ray, 1920-2012. (2001)
Green Town, Illinois is visited by a mysterious Mr. Dark and his Pandemonium Carnival. Terrifiying things begin to happen when two small boys become too curious about things.
Keywords: Carnivals -- Fiction; Illinois -- Fiction; Fiction